Peningkatan kompetensi menulis puisi siswa SMA dengan strategi Ekonek - Pramono, Teguh; Sumadi, Sumadi; Rofi'uddin, AH. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
Students’ writing competence at State Senior High School Pagak I in composing poetry is still low due to difficulties in brainstorming ideas and using poetic devices. Therefore, this classroom action research was conducted to develop students’ writing competence in composing poetry through the use of the Ekonek strategy (exploration, construction, elaboration, and confirmation), focusing on (1) idea extraction, (2) idea arrangement, and (3) imagery development, diction, theme and meaning, figures of speech, rhyme and rhythm, and typography. The subjects of this research were 20 students, consisting of three boys and 17 girls. The results show an increase in students’ competence, indicated by a gain of 25.88, from an average score of 56.14 on the first poetry test to 82.02 on the final test. This improvement also increased the number of students who reached the minimum mastery criterion (KKM), from 10.53% in the pre-cycle to 89.47% in the post-cycle.